EFL Students’ Perception of Distance Learning Practice in a Vocabulary Class - Ribeh Najib Muhammad (J-SHMIC : Journal of English for Academic, 2021)
The perception of English as a Foreign Language (EFL) students toward the significance of distance learning practice in EFL teaching at university is essential to provide suggestions for enhancing distance learning practice in the context of EFL teaching. Therefore, the purpose of this study was to investigate students’ perception towards distance learning practice at University of Muhammadiyah Gresik, especially in Words in Contexts class as the main course for learning vocabularies. Therefore, this study explored several aspects that needed in the implementation of distance learning practice. The subjects of this study were 34 first semester students of English education department who had applied distance learning practice. Questionnaire was used as research instrument to collect data from the respondents who had been selected. In addition, interview was also conducted to confirm the result of questionnaire. After the data were collected, they were analyzed using quantitative and qualitative analysis method. The finding indicated that students had average perception towards the implementation of distance learning practice, since distance learning practice provided advantages for their learning process. However, there were setbacks and problems such as students’ participation, internet connectivity, and material clarity that needed to be solved in order to improve the quality of distance learning practice.